Prisoners at ultra-high-risk for psychosis: a cross-sectional study. (3rd March 2015) - Jarrett, M.; Valmaggia, L.; Parrott, J.; Forrester, A.; Winton-Brown, T.; Maguire, H.; Ndegwa, D.; McGuire, P.; Craig, T. K. J.
Abstract : Background: The definition of ultra-high risk (UHR) for psychosis was derived from community-based help-seeking populations. Prisoners have high rates of psychosis and other severe mental health (MH) problems. They also have high rates of risk factors for psychiatric morbidity and yet they are among the populations who are less likely to seek help in the community. Despite a policy of equivalence of care for individuals in prison there are no early intervention services for psychosis in prisons in the UK. This was a study exploring feasibility of introducing such a service into a local London prison. This paper discusses the differences in MH profile of prisoners who met criteria for at-risk mental state compared with those who did not. Method: A two-stage procedure was used. Participants in a local London prison were routinely screened in the first week of arrival in prison with the Prodrome Questionnaire – Brief Version (PQ-B; Loewy et al. 2011). Those that screened positive as well as a small sample of those who screened negative underwent a further semi-structured assessment to see whether they met criteria for UHR state. Data on self-harm and suicide attempt, family psychiatric history, and anxiety and depression was also collected. Results: A total of 891 prisoners were screened, 44% of whom screened positive. A total of 354 underwent second stage assessment, 60 of whom had screened negative. Four groups were identified: those that had no MH problems, a group experiencing First Episode Psychosis, those at UHR of psychosis and a group with other MH problems. The UHR state and Psychotic groups had very similar MH profiles of symptoms and distress. Prisoners with no MH problems were at the other end of the spectrum with few symptoms and little distress. The Other group fell in between this group and the psychotic spectrum group in terms of symptomology and distress. Conclusions: This study is the first to examine risk for psychosis in an adult male prison population. We identified a broad spectrum of MH disorder for which there is little current service provision in prisons. Screening early in the custodial process has the potential to identify unmet MH need and has implications for keeping individuals safe in custody. A long-term strategic approach is required to address MH need in prisons.